Photoshop Elements 2020 For Dummies - Obermeier, Barbara; Padova, Ted (Learning made easy., 2019)
Go beyond one-click filters with Photoshop Elements 2020 Photoshop Elements offers the tools to make quick, simple fixes to photos or to turn your images into completely different pieces of art. Digital imaging pros Barbara Obermeier and Ted Padova walk you step-by-step through the tools that help you take control of this powerful software. Discover simple one-click fixes that repair the most basic photo problems then dive into creative editing and adding artistic touches. You'll also find tips on shooting better photos and managing common photo projects. Apply instant edits to your digital images Improve lighting and add some color pops Discover artistic filters that push your creativity Create a frame-worthy print This fun guide is here to provide help to photographers and designers who prefer the latest version of the lighter, less-expensive version of Photoshop.